Decentralized HIV testing: comparing peer and mail-based distribution strategies to improve the reach of HIV self-testing among people who use drugs in Florida - William H. Eger; Alexa Mutchler; Tim Santamour; Shelby Meaders; Heather A. Pines; Angela R. Bazzi; Hansel E. Tookes; Tyler S. Bartholomew (BMC, 2024)
Abstract Introduction People who use drugs (PWUD) are at increased risk for HIV infection. HIV self-testing (HIVST) is a promising method for identifying new infections, but optimal distribution strategies remain understudied. Methods To characterize PWUD by HIVST distribution strategy (peers vs. mail), we examined data from July 2022 to June 2023 collected from a real-world HIVST program led by the non-profit, Florida Harm Reduction Collective. We used descriptive statistics and Poisson regressions with robust error variance to compare those who received HIVST through peers or via mail by socio-demographics, Ending the HIV Epidemic (EHE) county designation, and HIV testing experience. Results Among 728 participants, 78% received HIVST from peers, 47% identified as cisgender female, 48% as heterosexual, and 45% as non-White; 66% resided in an EHE county, and 55% had no HIV testing experience. Compared to those who received an HIV self-test from peers, those who received tests via mail were less likely to be cisgender male (vs. cisgender female; prevalence ratio [PR] = 0.59, 95% confidence interval [CI]: 0.43, 0.81), non-Hispanic Black (vs. non-Hispanic White; PR = 0.57, 95% CI: 0.36, 0.89) or from EHE counties (vs. non-EHE counties; PR = 0.33, 95% CI: 0.25, 0.44). Those who received tests via mail were also more likely to identify their sexual orientation as "Other/Undisclosed" (vs. straight/heterosexual; PR = 2.00, 95% CI: 1.51, 2.66). Conclusion Our findings support the role of community-based HIVST distribution strategies in increasing HIV testing coverage among PWUD. Additional research could help inform the equitable reach of HIVST.